The marine biogeochemistry of dissolved and colloidal iron - Fitzsimmons, Jessica Nicole (Massachusetts Institute of Technology, 2013)
Thesis (Ph. D.)--Joint Program in Chemical Oceanography (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2013. Cataloged from PDF version of thesis. Includes bibliographical references. Iron is a redox active trace metal micronutrient essential for primary production and nitrogen acquisition in the open ocean. Dissolved iron (dFe) has extremely low concentrations in marine waters that can drive phytoplankton to Fe limitation, effectively linking the Fe and carbon cycles. Understanding the marine biogeochemical cycling and composition of dFe was the focus of this thesis, with an emphasis on the role of the size partitioning of dFe (<0.2 jm) into soluble (sFe<0.02 jm) and colloidal (0.02ptm<cFe<0.2 m) size fractions. This was accomplished through the measurement of the dFe distribution and size partitioning along basin-scale transects experiencing a range of biogeochemical influences. dFe provenance was investigated in the tropical North Atlantic and South Pacific Oceans. In the North Atlantic, elevated dFe (>I nmol/kg) concentrations coincident with the oxygen minimum zone were determined to be caused by remineralization of a high Fe:C organic material (vertical flux), instead of a laterally advected low oxygen-high dFe plume from the African margin. In the South Pacific Ocean, dFe maxima near 2000m were determined by comparison with dissolved manganese and 3He to be caused by hydrothermal venting. The location of these stations hundreds to thousands of kilometers from the nearest vents confirms the "leaky vent" hypothesis that enough dFe escapes precipitation at the vent site to contribute significantly to abyssal dFe inventories. The size partitioning of dFe was also investigated in order to trace the role of dFe composition on its cycling. First, the two most commonly utilized methods of sFe filtration were compared: cross flow filtration (CFF) and Anopore filtration. Both were found to be robust sFe ...